2012
DOI: 10.4082/kjfm.2012.33.3.174
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Use of Uterine Cervical Cancer Screening Services in Korean Elderly Women

Abstract: BackgroundThe Papanicolaou (Pap) smear test is an effective screening test for the early detection of uterine cervical cancer. The Pap test still plays an important role in Korean elderly women, as uterine cervical cancer remains a frequent form of cancer and an important cause of death. However, the participation rate and other factors related to the Pap test in Korean elderly women have been studied insufficiently.MethodsThis study included 654 individuals aged 65 and over who completed a cervical cancer scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Different from the present study; in the studies the rate of having pap smear was found to increase as the educational level increased. [16][17][18] In Kalyoncu's study, 68.9% of the offi cers, which were the group with the highest rate of having smear test; whereas, this rate was found to be 18.9% in doctors. 19 The fact that the rate of having smear test signifi cantly decreased with higher educational level was associated with high awareness related to risk factors in cervical cancer, the use of barrier methods, virginity, and monogamy in active sexual life.…”
Section: Discussionmentioning
confidence: 98%
“…Different from the present study; in the studies the rate of having pap smear was found to increase as the educational level increased. [16][17][18] In Kalyoncu's study, 68.9% of the offi cers, which were the group with the highest rate of having smear test; whereas, this rate was found to be 18.9% in doctors. 19 The fact that the rate of having smear test signifi cantly decreased with higher educational level was associated with high awareness related to risk factors in cervical cancer, the use of barrier methods, virginity, and monogamy in active sexual life.…”
Section: Discussionmentioning
confidence: 98%
“…We adopted six binary outcome variables to measure the use of preventive healthcare service that is in line with existing national guidelines. These include the regular medical check-up [25], stomach cancer screening, colon cancer screening, cervical cancer screening [32], and breast cancer screening within the past two years [33], as well as the influenza vaccination in the previous year [34]. Among the 16,964 respondents for each question, three answered “unsure” whether they had the influenza vaccine or not within the given period.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding the factors influencing the uptake of CCS is important to increase the screening rates and improve the prognosis of cervical cancer. Previous studies in Korea on CCS and its influencing factors have reported various socioeconomic factors with inclusion of age, income, education, region of residence, occupation, marital status, and family history of cervical cancer, as contributing to inequalities in the screening rate [ 8 9 10 11 12 ]. However, these studies were based on cross-sectional design using the Korean National Health and Nutrition Examination Survey (KNHANES) and the Korea National Cancer Screening Survey, which only captured the uptake of CCS at a single time point, making it difficult to obtain information on the regular uptake of CCS over a long-term period.…”
Section: Introductionmentioning
confidence: 99%